Non-host Plant Resistance against Phytophthora capsici Is Mediated in Part by Members of the I2 R Gene Family in Nicotiana spp. - Vega-Arreguín, Julio C.; Shimada-Beltrán, Harumi; Sevillano-Serrano, Jacobo; Moffett, Peter (Frontiers in Plant Science, 2017)
Abstract The identification of host genes associated with resistance to Phytophtora capsici is crucial to developing strategies of control against this oomycete pathogen. Since there are few sources of resistance to P. capsici in crop plants, non-host plants represent a promising source of resistance genes as well as excellent models to study P. capsici – plant interactions. We have previously shown that non-host resistance to P. capsici in Nicotiana spp. is mediated by the recognition of a specific P. capsici effector protein, PcAvr3a1 in a manner that suggests the involvement of a cognate disease resistance (R) genes. Here we have used virus-induced gene silencing (VIGS) and transgenic tobacco plants expressing dsRNA in Nicotiana spp to identify candidate R genes that mediate non-host resistance to P. capsici. Silencing of members of the I2 multigene family in the partially resistant plant N. edwardsonii and in the resistant N. tabacum resulted in compromised resistance to P. capsici. VIGS of two other components required for R gene-mediated resistance, EDS1 and SGT1, also enhanced susceptibility to P. capsici in N. edwardsonii, as well as in the susceptible plants N. benthamiana and N. clevelandii. The silencing of I2 family members in N. tabacum also compromised the recognition of PcAvr3a1. These results indicate that in this case, non-host resistance is mediated by the same components normally associated with race-specific resistance.